2017
DOI: 10.2116/analsci.33.313
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Injection Chromatography with an Ultra-short Monolithic Column for the Low-Pressure Separation of α-Tocopherol and γ-Oryzanol in Vegetable Oils and Nutrition Supplements

Abstract: A low-pressure separation procedure of α-tocopherol and γ-oryzanol was developed based on a sequential injection chromatography (SIC) system coupled with an ultra-short (5 mm) C-18 monolithic column, as a lower cost and more compact alternative to the HPLC system. A green sample preparation, dilution with a small amount of hexane followed by liquid-liquid extraction with 80% ethanol, was proposed. Very good separation resolution (Rs = 3.26), a satisfactory separation time (10 min) and a total run time includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…8 Thaithet et al reported on sequential injection chromatography (SIC) using an ultra-short monolithic column for the separation of α-tocopherol and γ-oryzanol in edible oils and nutrition supplements. 9 The total analysis time, including column equilibration, is 16 min, and the obtained results agree well with the results from HPLC. At first, the application of SIC was limited to the determination of pharmaceutical samples; now it has been expanded to various samples, such as biological, food, and environmental analyses.…”
supporting
confidence: 81%
“…8 Thaithet et al reported on sequential injection chromatography (SIC) using an ultra-short monolithic column for the separation of α-tocopherol and γ-oryzanol in edible oils and nutrition supplements. 9 The total analysis time, including column equilibration, is 16 min, and the obtained results agree well with the results from HPLC. At first, the application of SIC was limited to the determination of pharmaceutical samples; now it has been expanded to various samples, such as biological, food, and environmental analyses.…”
supporting
confidence: 81%